Effects of Peer Support Program on Self-Management in Patients with End-Stage Renal Disease Undergoing Hemodialysis - Husain, Fida'; Kusuma, Henni; Johan, Andrew (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: End-stage renal disease (ESRD) patients undergoing hemodialysis require essential self-management to lifestyle changes to minimize the risk of complications, morbidity, and mortality. Efforts made to improve self-management of hemodialysis patients in previous studies were carried out by health workers that may not provide 'real' knowledge, while peer support programs carried out by patients as peers to share their experiences may provide more benefits.Purpose: The purpose of this study was to determine the effects of peer support programs on improving self-management in patients with ESRD undergoing hemodialysis.Methods: This study employed a quasi-experimental design and involved a total of 33 patients in the control group and 32 patients in the intervention group, who met the inclusion and exclusion criteria. The samples were recruited consecutively. The intervention of peer support programs was implemented through information support, emotional support, and mutual reciprocity in groups of 10-12 people to share experiences related to their self-management. The intervention was given for six sessions; each lasted for 30-45 minutes. The data were collected using the Indonesian version of the hemodialysis self-management instrument (HDSMI) and analyzed using a paired-sample t-test and independent-sample t-test.Results: The results showed that after the intervention, the mean score of self-management in the intervention group increased from 79.47±7.919 to 90.75±7.089, and in the control group, the mean increased from 81.88±8.291 to 82.12±7.692. After the implementation of peer support programs, there was a significant difference in the score of self-management between the intervention and control groups (p<0.001).Conclusion: Peer support programs gave an effect on increasing self-management in patients with ESRD undergoing hemodialysis. Peer support programs should be introduced early to ESRD patients undergoing hemodialysis so that they can learn about self-management from other patients.